2018
DOI: 10.1128/aem.00539-18
|View full text |Cite
|
Sign up to set email alerts
|

LEA Proteins and the Evolution of the WHy Domain

Abstract: The late embryogenesis abundant (LEA) family is composed of a diverse collection of multidomain and multifunctional proteins found in all three domains of the tree of life, but they are particularly common in plants. Most members of the family are known to play an important role in abiotic stress response and stress tolerance in plants but are also part of the plant hypersensitive response to pathogen infection. The mechanistic basis for LEA protein functionality is still poorly understood. The group of LEA 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 57 publications
0
39
0
4
Order By: Relevance
“…LEA14-like protein families containing a conserved WHy (water stress and hypersensitive response) domain (78) were acquired in LACAOA, in CARA, and repeatedly during AOA diversification, ending up with multiple copies in extant genomes (Fig. 4, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LEA14-like protein families containing a conserved WHy (water stress and hypersensitive response) domain (78) were acquired in LACAOA, in CARA, and repeatedly during AOA diversification, ending up with multiple copies in extant genomes (Fig. 4, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that sucrose glasses are stabilized in vitro by interaction with LEA proteins [46]. A recent phylogenetic analysis suggests that the LEA protein from plants may have ancestral origins in the domains Bacteria and Archaea with acquisition endosymbionts or horizontal gene transfer [44]. Thus, it is not surprising that overexpression of LEA protein from plants increased tolerance against abiotic stresses in microorganisms [20,45].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we identified a late embryogenesis abundant (LEA) gene within the region on Chr8 that influences both root biomass and TRL under stressed conditions (i.e., Root.Biomass.8.1 and TRL.8.1). This protein family has a strong association with abiotic stress responses, particularly related to dehydration stress (e.g., [ 132 , 133 ]) Indeed, it is involved in multiple relevant processes, including combating stress-derived ROS responses and maintaining membrane stability during periods of water loss [ 132 , 134 136 ].…”
Section: Discussionmentioning
confidence: 99%